2015
DOI: 10.1007/s12471-015-0773-7
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic evaluation of alternative left ventricular endocardial pacing sites in clinical non-responders to cardiac resynchronisation therapy

Abstract: IntroductionNon response to cardiac resynchronisation therapy (CRT) may be related to the position of the coronary sinus lead.MethodsWe studied the acute haemodynamic response (AHR) from alternative left ventricular (LV) endocardial pacing sites in clinical non-responders to CRT. AHR and the interval from QRS onset to LV sensing (Q-LV interval) from four different endocardial pacing sites were evaluated in 24 clinical non-responders. A rise in LVdP/dtmax ≥ 15 % from baseline was considered a positive AHR. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Crucially, in 96.8% of patients, the optimal hemodynamic performance was associated with delivering pacing therapy at the site exhibiting the LEA. A similar figure (85%) was observed by van Gelder et al in their evaluation of the effects of LV endocardial pacing amongst a cohort of non-responders to epicardial CRT [102]. The small discrepancy may be attributed to the larger cohort of ischemic patients in this study.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)supporting
confidence: 86%
“…Crucially, in 96.8% of patients, the optimal hemodynamic performance was associated with delivering pacing therapy at the site exhibiting the LEA. A similar figure (85%) was observed by van Gelder et al in their evaluation of the effects of LV endocardial pacing amongst a cohort of non-responders to epicardial CRT [102]. The small discrepancy may be attributed to the larger cohort of ischemic patients in this study.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)supporting
confidence: 86%
“…The percentage of nonresponders (8.5%) included in the series that we initiated in April 2011 is much lower than what was observed in ALSYNC study (23%) because we began to include previous nonresponders in late 2015. This clinical decision was initially based on a case report published by Bracke et al, then strengthened by the good results obtained in nonresponders by ALSYNC investigators and first reported at Heart Rhythm 2014; additional evidence was provided by Van Gelder in 2016 …”
Section: Discussionmentioning
confidence: 99%
“…Bracke et al published a successful protocol (using dP/dTmax measurements) to assess the acute hemodynamic (AHR) response of alternative LV endocardial pacing sites, as compared to the implanted CS‐epicardial system, in one nonresponder patient . The same team studied 24 clinical nonresponders using improvements in dP/dTmax and the Q‐LV interval to measure the AHR of different LV endocardial sites . Behar et al combined magnetic resonance imaging, electroanatomic contact mapping, and AHR studies, reporting the superiority of endocardial pacing over epicardial venous pacing when both were optimized using AHR.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines that QRS absolute width itself may not reflect the real pattern of conduction delay to the LV, which instead may be measured by the Q-LV interval. The Q-LV interval is defined as the interval from the onset of the intrinsic QRS on 12-lead surface ECG to the first large positive or negative peak of the LV EGM [18].…”
Section: Pacing Timing In Crtmentioning
confidence: 99%